Estudos fisiológicos e bioquímicos para criopreservação de embriões zigóticos de Coqueiro Anão Verde de Jiqui do Brasil - Copeland, Kicia Karinne Pereira Gomes (2010)
The culture of coconut (Cocos nucifera L.) has a significant importance in generating employment and income throughout all the year. The in vitro germplasm banks offer several benefits, such as high rates of multiplication, production of arrays free of pathogens, reduction of genetic erosion, reduced demand for space, cost savings with the workforce and facilitating international exchange of germplasm. Therefore, the long-term conservation address these needs, but can also be used to keep recalcitrant and intermediate species. This paper aims at the long-term retention of mature zygotic embryos of dwarf green coconut-tree Jiqui of Brazil (Cocos nucifera L.) in liquid nitrogen at -196 celcius degrees; adapt the application of tetrazolium tests, electrical conductivity and potassium leaching to study the feasibility of cryopreserved embryos and to analyze the viability of embryos after cryopreservation. Zygotic embryos of fruits from a planting of dwarf green coconut-tree Jiqui of Brazil (AveJBr) with 10 at 11 months of maturation were used. Endosperm cylinders with zygotic embryos were placed in sterile containers and sent to the Plant Tissue Culture Laboratory of Embrapa Coastal Tablelands, Aracaju, Sergipe. We evaluated the effects of different periods of dehydration, treatment of cryoprotectants and drying methods on moisture from embryos using the methodology of Assy-Bah & Engelmann (1992) and CPATC methodology. Electrical conductivity tests, potassium leaching and tetrazolium were performed to evaluate the feasibility of zygotic embryos after cryopreservation. After selecting the adapted method from dehydration, AveJBr coconut zygotic embryos were cryopreserved and after 48 hours underwent to a recovery stage in culture medium Y3 liquid. The CPATC methodology with the initial dehydration of embryos in cryoprotectant and subsequent drying in silica gel for four hours promotes lower humidities in mature zygotic embryos of coconut AveJBr. The pre-treatment of mature zygotic embryos of coconut AveJBr with cryoprotectant with 1.75 mol L-1 sucrose + 15% glycerol for 12 and 16 hours promotes lower humidity of the embryos, but also higher viability in electrical conductivity , potassium leaching and tetrazolium. Samples with 10 embryos are sufficient for analysis of electrical conductivity in zygotic embryos of coconut AveJBr not cryopreserved. The incubation period of four to eight hours of embryos is promising for the electrical conductivity analysis in mature zygotic embryos of coconut AveJBr not cryopreserved. The concentration of 0.25% of tetrazolium is indicated for the viability analysis of mature zygotic embryos of coconut AveJBr not cryopreserved. The period of 90 days is not sufficient to the germination evaluation of cryopreserved embryos.